The bad mood and the stick - Snicket, Lemony; Forsythe, Matthew, 1976- (New York : Little, Brown and Company, 2017)
Curly's bad mood travels from person to person, unexpectedly leaving opportunities for forgiveness, laughter, and love in its wake.
Keywords: Mood (Psychology) -- Juvenile fiction; Conduct of life -- Juvenile fiction; Emotions -- Juvenile fiction; Mood (Psychology) -- Fiction; Behavior -- Fiction; Emotions -- Fiction; JUVENILE FICTION / Social Themes / Emotions & Feelings; JUVENILE FICTION / Social Themes / Manners & Etiquette; Emotions -- Fiction; Mood (Psychology) -- Fiction; Behavior -- Fiction